Preachers' Perspective about Content Manipulation for Da’wah on Social Media - Muh. Azhar Mubarak (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
The technology available on social media provides various conveniences that can be utilized to optimize the implementation of Da’wah. One such technology is the editing feature. However, this feature can also cause the meaning of the message conveyed by the original content. Therefore, this research aims to investigate the perspective of preachers (da’i) on the phenomenon of manipulating da’wah content to conform to the format desired by social media platforms. This research applies a descriptive qualitative method in which data is obtained through in-depth interviews with six preachers who are postgraduate students at UIN Alauddin Makassar in 2022. The research results show that before spreading short-duration da’wah content on social media, preachers strive to understand the content by conducting discussions with other preachers, examining the content, and comparing content that has undergone editing (cutting) and original content. This is done as a precautionary measure to prevent misunderstandings among the audience and identify possible deviations caused by the editing process.